Development of Flame Retardant Stearic Acid Doped Graphite Powder and Magnesium Hydroxide Nanoparticles, Material for Thermal Energy Storage Applications. Issue 1 (1st January 2022) - Han, Kyaw Thet; Lhosupasirirat, Siraprapa; Srikhirin, Pongsid; Houngkamhang, Nongluck; Srikhirin, Toemsak
Abstract: Nano-enhanced organic phase change material (PCM) composite consists of stearic acid (SA, act as the thermal storage media), graphite powder(GP, function as thermal conductor), and magnesium hydroxide nanoparticles(nMH), micro-sized (MMH), function as the flame retarder), were formulated and investigated for their thermophysical properties and flammability. The flame-retardant properties of nano-enhanced composite PCM were evaluated by using the burning test. Phase change temperature, phase change latent heat, and thermal conductivity were obtained by the T-history method. To reduce the flammability, 5wt% of MH with 0.8μm and 200nm were added to PCMs. 1wt% of GP improved thermal conductivity of stearic acid from 0.245 to 0.4887 W/mk, and doping of flame-retardant nanoparticles to PCM showed the reduction of flammability and slightly effecting on latent heat of PCM. nMH were found to work better for stearic acid flammability than MMH, where combustion time of 0.1g pure stearic acid(SA) was decreased from 41s to 17s and 23s. For nano-sized(SA/nMH) and micron-sized(SA/MMH)composites, the latent heat of pure PCM dropped from 171.26 to 124.85KJ/kg, but micron-sized addition negatively affects latent heat values by reducing from 171.26 to 88.87 KJ/kg. The results confirmed that nMH/GP/SA composite could reduce flammability without showing a negative impact on storage capacity.